Intervenciones de enfermería para el manejo del dolor agudo en pacientes pediátricos - Aida Jimena, Changoluisa Chillagana (2021)
ABSTRACT Pain in children is a public health problem of global importance, since it is linked to physical suffering with the consequent repercussions on a psychological, social and spiritual level. Acute pain is defined as: “an unpleasant sensory and emotional experience that is associated with a current or potential tissue injury”; being necessary for its approach a wide field of knowledge destined to its assessment and relief. With this background, a quantitative, descriptive and cross-sectional study was carried out in a second-level hospital with the participation of 6 professionals and 38 nursing students, with the aim of determining the interventions for the management of acute pain in pediatric patients by identifying the use of assessment tools, attitudes, practices and training of nursing staff, to establish a care plan oriented to children older than 36 months who experience pain, using the NANDA, NOC and NIC taxonomies. It was developed in two phases, the first corresponds to the application of an observation using a card designed by Moraes; In the second phase, an instrument aimed to manage children older than 36 months pain was applied. It is concluded that the practices and attitudes of nursing professionals and students are consistent with adequate pain management. KEY WORDS: Pediatric Nurses, Acute Pain, Pharmacological Treatment Reviewed by: MsC. Edison Damian Escudero ENGLISH PROFESSOR C.C.0601890593